2018
DOI: 10.1590/s1980-220x2017038803352
|View full text |Cite
|
Sign up to set email alerts
|

Aferição do volume residual gástrico: retrato da prática clínica de enfermeiros

Abstract: We can highlight the need for nurses' training and further studies focused on the practice for assessing gastric residual volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…In a systematic review of 72 studies, the FI was defined based on a large GRV in most of the studies [5] . Although it is recommended by ASPEN guidelines that EN should not be withheld for a GRV of <500 mL, the median GRV threshold reportedly used in clinical practice was 200 to 250 (range, 75–500) mL, which was considered large [5,8–14] . Monitoring GRV and holding or interrupting EN for a large GRV is one of the most conventional and widely accepted nursing practices in the ICU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic review of 72 studies, the FI was defined based on a large GRV in most of the studies [5] . Although it is recommended by ASPEN guidelines that EN should not be withheld for a GRV of <500 mL, the median GRV threshold reportedly used in clinical practice was 200 to 250 (range, 75–500) mL, which was considered large [5,8–14] . Monitoring GRV and holding or interrupting EN for a large GRV is one of the most conventional and widely accepted nursing practices in the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Although it is recommended by ASPEN guidelines that EN should not be withheld for a GRV of <500 mL, the median GRV threshold reportedly used in clinical practice was 200 to 250 (range, 75-500) mL, which was considered large. [5,[8][9][10][11][12][13][14] Monitoring GRV and holding or interrupting EN for a large GRV is one of the most conventional and widely accepted nursing practices in the ICU. However, owing to the lack of a standard monitoring method, it has been reported that GRV assessment does not accurately reflect the total volume of the contents available, and the value of the measured volume could be influenced by many factors, including investigator-related and tube-related factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, returning residual gastric aspirates can improve the management of nutrition delivery and balance of fluid and electrolyte; however, this process is prone to higher risk of tube blockage and contamination [9, 29]. It’s well-known that discarding the residual gastric aspirates can increase the risk of reducing energy intake, however, the very abnornal looking aspirates such as bloody, fecal or very bilious aspirates are virtually always discarded since it’s a sign of gastric bleeding or intolerance [30]. The present study did not found any difference between the return and discard intervention in terms of the average potassium level, the episodes of gastric emptying delay, and related adverse complications.…”
Section: Discussionmentioning
confidence: 99%
“…Em pacientes com intolerância gastrointestinal, alto risco de aspiração ou aumento do suporte vasopressor, é aconselhável a NP. Em pacientes com distensão gástrica e gastrite erosiva, devem ser considerados o uso de NP suplementar ou de fórmulas entéricas altamente digeríveis, específicas e hiperproteicas, enriquecidas com ácidos graxos ω-3 e/ou com outros nutrientes anti-inflamatórios e imunomoduladores, a exemplo do Zn e vitamina D (Calder et al, 2010;Poveda et al, 2018). Ressalta-se que na COVID-19, a decisão por instituir a NP deve ser cautelosa, bem como deve ser prioridade oferecer imunonutrientes por esta via, como tentativa de compensar o seu efeito deletério na morfologia e resposta imune (Gutiérrez et al, 2019;Huang et al, 2020).…”
Section: Terapia Nutricional Em Pacientes Com Covid-19unclassified